Pengembangan Agribisnis Ikan Tembang Putih (Clupeiodes Lile) Di Kabupaten Pasuruan Propinsi Jawa Timur - Mimit Primyastanto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2019)
One of the potential product is Clupeiodes lile. Clupeiodes lile is an export commodity in Singapore, Malaysia, and Japan. Now, Demands for Clupeiodes lile has been increased by the buyer. From this, a needed improvement on technical development, fast and precise handling for stabilizing the quality of Clupeiodes lile . This project is planning on two home industries, Home industry (UD) Surya Abadi (SA) and Home Industry (UD) HCR at Jatirejo and Pasinan Village. This project was done with the spacious survey, interview, and observation. The problems on two home industries are sanitation and hygiene was not appropriating with export standard and conventional manufacturing. Now, this project gives an efficient technology such as TTG Mechanically Dryer Green House Model. From this technology, expectable that home industries can produce the best Clupeiodes lile from long durability, best sanitizer and hygiene, and can increase the home industries' profit.